Energy consumption modelling of a passive hybrid system for office buildings in different climates. (15th January 2022) - Zhang, Yi; Tennakoon, Thilhara; Chan, Yin Hoi; Chan, Ka Chung; Fu, Sau Chung; Tso, Chi Yan; Yu, Kin Man; Huang, Bao Ling; Yao, Shu Huai; Qiu, Hui He; Chao, Christopher Y.H.
Abstract: Thermochromic smart windows and radiative coolers are two passive cooling technologies, whose adoption as windows and roofs, respectively, is feasible for building energy-saving. However, to the authors' knowledge, the investigation of annual energy performance incorporating both techniques is scarce at the time of writing. Therefore, a passive hybrid system involving both technologies is proposed in this study. A perovskite thermochromic smart window and three different radiative coolers were chosen based on their superior performance. The energy performance of the passive hybrid system in a prototypical medium-sized office building was simulated using EnergyPlus and the results were rigorously analyzed. Both thermochromic smart window and radiative cooler could reduce total energy consumptions by up to 10.6% and 23.0%, respectively, regardless of building's year of completion, while the synergic system saved up to 32.0%. Among the chosen cities of various climates, thermochromic smart windows and radiative coolers perform better in cities where cooling demand dominates. The west- and east-facing thermochromic smart windows could mitigate more energy usage in contrast to the other orientations. If this passive hybrid system can be offered at a reasonable cost, the technology is likely to be a viable energy-efficient option for buildings. Highlights: The building energy saving performance of a passive hybrid system was simulated. The hybrid system can save energy for both new and old buildings. The hybrid system is favorable to use in hot climates. The east and west facing smart windows show the greatest energy saving potentials. Applying the hybrid system saves the building total energy up to 32%.